Development of a simulation approach to the management of aircraft rotable spare parts - Al-Anezi, M. (Cranfield University, 1997)
A simulation model has been developed for the effective management of aircraft rotable spare parts. The model was based on real data obtained from airlines representing various processes and functions of the airlines maintenance operations. The main processes that were thoroughly discussed were failure and repair turnaround time representing the demand and supply of spare parts systems. Results of the simulation model have been compared to those of the standard method for the objective of establishing a level of confidence of results of the simulation model, and that helped to enhance the understanding of service level, and the assumptions behind the standard method. The developed model is more realistic with regard to estimating requirements of aircraft rotable spare parts, and have the advantage of being able to consider important management policies that were not considered in the standard method.